(untitled) (Indian Journal of Chemistry (IJC), 2025)
• In this paper, the research on the synthesis of magnesium-zinc-phthalocyanine pigment was carried out. It was synthesized based on phthalic anhydride, urea, zinc acetate, and magnesium acetate. The mole ratio of the initial substances was taken in the ratio of 1:4:3, and it was synthesized with a yield of 89.5% and carried out at a temperature of 2250C. The structure of this obtained pigment was analyzed by IR spectral analysis of this pigment based on magnesium and zinc phthalocyanine, it was found that the formation of phthalocyanine rings gives a peak in the region of 744.52-792.74 cm-1, while the benzene rings give a peak in the region of 975.98 cm-1. Its thermal stability by thermogravimetric analysis, SEM (scanning electron microscope), EDS, and elemental analysis. According to the results of the analysis, it was confirmed that magnesium-zinc phthalocyanine was synthesized by forming phthalocyanine rings.